2013 Benjamin Franklin Medal in Life Science presented to Rudolf Jaenisch. Issue 7 (July 2015) - Ferrone, Frank A.
Abstract The discovery of the genetic code established that the sequence of base-pairs within DNA contains the instructions for regenerating the organism from which the DNA came, and is transmitted from generation to generation. It therefore came as a surprise that there were also heritable controls for gene expression that were independent of the DNA sequence information. This is known as epigenetics, and is mainly controlled by methylation of DNA. Rudolf Jaenisch played a pivotal role in establishing the nature of such epigenetic control, and showing that it is also featured in cancers as well as normal development. Moreover, he has shown how these epigenetic mechanisms may be controlled to allow cells to be cloned, giving the hope of someday being able to regenerate damaged or diseased organs.